Synthesis and characterization of aromatic copolyesters containing siloxane linkages in the polymer backbone - Waghmare, P. B.; Idage, Susheela B.; Menon, Shamal K.; Idage, Bhaskar B. (Journal of Applied Polymer Science, 2006)
A new series of aromatic copolyesters containing siloxane linkages were prepared by the melt polymerization of bisphenol A (BPA) with eugenol end-capped siloxane (EuSi), diphenyl terephthalate (DPT), and diphenyl isoplithalate (DPI) in varying ratio in the temperature range 220-290 degrees C under reduced pressure in the presence of dibutyl tin dilaurate (DBTL) catalyst. The siloxane copolyesters prepared were characterized by FTIR, H-1-NMR spectroscopy, solution viscosity, thermogravimetric analysis, differential scanning calorimetry, and X-ray diffraction. The effect of incorporation of eugenol end-capped siloxane was studied on the properties of BPA/DPI/DPT copolyesters. The glass-transition temperature of copolyester was decreased from 184 to 70 degrees C by incorporation of 20% of eugenol endcapped siloxane. All copolyesters were found to be soluble in commonly used aprotic polar solvents and had film-forming properties. (c) 2006 Wiley Periodicals, Inc.
Keywords: aromatic copolyesters; Bisphenol A; diphenyl isophthalate; diphenyl terephthalate; eugenol end-capped siloxane; melt polymerization

Synthesis and characterization of copolyarylates using tin octoate as a catalyst - Waghmare, P. B.; Pathak, P.; Deshmukh, S. A.; Idage, Susheela B.; Idage, Bhaskar B. (Journal of Applied Polymer Science, 2006)
A series of copolyarylates of bisphenol A (BPA) with varying ratios of diphenyl terephthalate (DPT) and diphenyl isophthalate (DPI) were prepared by melt polymerization at a temperature ranging from 200 to 290 degrees C under reduced pressure in the presence of tin octoate catalyst. Tin octoate catalyst has been extensively used for the preparation of biodegradable polymers namely, poly(lactic acid), poly(glycolic acid), and poly(lactide-glycolide) copolyesters. However, there are no reports on the preparation of copolyesters by melt polymerization using tin octoate catalyst. The effect of tin octoate catalyst was studied on the preparation of BPA/DPT/DPI copolyarylates. The copolyarylates were characterized by infrared and H-1 NMR spectroscopy, solution viscosity, thermogravimetric analysis, differential scanning calorimetry, and X-ray diffraction. The solution viscosities of copolyarylates were varied from 0.43 to 0.56 dL/g and the glass transition temperature (T-g) of copolyarylates was varied from 155 to 222 degrees C by varying the ratio of DPT and DPI. Most of the copolyarylates were found to be soluble in commonly used organic solvents and had film-forming properties. (c) 2006 Wiley Periodicals, Inc.
Keywords: copolyarylates; diphenyl isophthalate; diphenyl terephthalate; melt polymerization; tin octoate

Synthesis and characterization of siloxane copolyesters containing phenylindane linkages - Waghmare, P. B.; Deshmukh, S. A.; Idage, Susheela B.; Idage, Bhaskar B. (Journal of Applied Polymer Science, 2006)
A novel series of siloxane copolyesters containing 1,1,3-trimethyl-3-(p-hydroxyphenyl)-5-indanol (phenylindane bisphenol), diphenyl terephthalate (DPT), diphenyl isophthalate (DPI), and eugenol end-capped siloxanes in varying ratios were prepared at a temperature range of 200-290 degrees C under reduced pressure using dibutyl tin dilaurate catalyst by melt polycondensation. The siloxane-containing copolyesters were characterized by infrared and H-1 NMR spectroscopy, elemental analysis, solution viscosity, thermogravimetric analysis, differential scanning calorimetry, and X-ray diffraction. The effect of incorporation of siloxane moiety was studied on the properties of phenyl indane/DPT/DPI coplyester. The glass transition temperatures of copolyesters were decreased from 235 to 124 degrees C by incorporation of 10% eugenol end-capped siloxane without affecting the thermal properties. All copolyesters were found to be soluble in commonly used organic solvents and had film forming properties. (c) 2006 Wiley Periodicals, Inc.
Keywords: eugenol end capped siloxane; melt polymerization; phenylindane bisphenol; siloxane copolyesters

Ring opening polymerization of dilactide using salen complex as catalyst - Idage, Bhaskar B.; Idage, Susheela B.; Kasegaonkar, A. S.; Jadhav, R. V. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2010)
The recent concerns about our environment have led to search for environmentally benign and sustainable materials that could substitute the more commonly used petroleum based materials. Biodegradable and sustainable polylactide (PLA) is becoming one of the most promising and practical materials as a partial replacement for the petroleum-based materials. The commercially available PLA is generally homochiral poly(L-lactide) (PLLA) at present because L-lactic acid with high optical purity can only be obtained in bulk by fermentation of carbohydrate. PLLA is mostly synthesized by ring opening polymerization (ROP) of homochiral L-lactide (LLA), which is a cyclic dimer of L-lactic acid. In the present work, poly(L-lactide)s were synthesized by the ring opening polymerization (ROP) of L-lactide using iron and manganese salen complexes as catalyst. The new iron and manganese salen complexes were synthesized, purified, characterized and used as catalyst for polymerization of L-lactide. The poly(L-lactide)s prepared were characterized by infrared, proton NMR spectroscopy, solution viscosity, gel permeation chromatography, thermal analysis and X-ray diffraction. (C) 2009 Elsevier B.V. All rights reserved.
Conference on Specialty Advanced Materials and Polymers for Aerospace and Defense and Applications (SAMPADA-2008), Mat Res Soc Singapore, Singapore, SINGAPORE, JUL 03-08, 2005
Keywords: Gel permeation chromatography; Iron salen catalyst; L-Lactic acid; L-Lactide; Manganese salen catalyst; Poly(L-lactide); ring opening polymerization; Solution viscosity

Synthesis and characterization of well-defined random and block copolymers of epsilon-caprolactone with l-lactide as an additive for toughening polylactide: Influence of the molecular architecture - Deokar, Megha D.; Idage, Susheela B.; Idage, Bhaskar B.; Sivaram, Swaminathan (Journal of Applied Polymer Science, 2016)
Well-defined multiarmed star random and block copolymers of epsilon-caprolactone with l-lactide with controlled molecular weights, low polydispersities, and precise numbers of arms were synthesized by the ring-opening polymerization of respective cyclic ester monomers. The polymers were characterized by H-1-NMR and C-13-NMR to determine their chemical composition, molecular structure, degree of randomness, and proof of block copolymer formation. Gel permeation chromatography was used to establish the degree of branching. Star-branched random copolymers exhibited lower glass-transition temperatures (T-g's) compared to a linear random copolymer. When the star random copolymers were melt-blended with poly(l-lactic acid) (PLA), we observed that the elongation of the blend increased with the number of arms of the copolymer. Six-armed block copolymers, which exhibited higher T-g's, caused the maximum improvement in elongation. In all cases, improvements in the elongation were achieved with no loss of stiffness in the PLA blends. (c) 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2016, 133, 43267.
Keywords: biodegradable; copolymers; differential scanning calorimetry; mechanical properties; ring-opening polymerization

Tailoring the properties of mPEG-PLLA nanoparticles for better encapsulation and tuned release of the hydrophilic anticancer drug - Surwase, Sachin S.; Munot, Neha Manish; Idage, Bhaskar B.; Idage, Susheela B. (Drug Delivery and Translational Research, 2017)
Gemcitabine is used as a first-line drug for treating many solid tumours. However, it suffers from a major drawback of strong side effects and short plasma half-life because of degradation by enzyme when administered intravenously. Polyesters and copolyesters are the most widely used and preferred class of biodegradable polymer. In the present work, efforts have been made to prepare poly(ethylene glycol) monomethoxy ether-poly(l-lactide) (mPEG-PLLA), a biodegradable amphiphilic copolymer with a view to improve the entrapment and tuned release of hydrophilic drug gemcitabine. The different mPEG-PLLA copolymers were synthesized with the varying ratios of mPEG and characterized by different techniques namely FTIR and ¹H NMR spectroscopy, solution viscosity, differential scanning calorimetry (DSC) and gel permeation chromatography (GPC). Gemcitabine-loaded nanoparticles were prepared using mPEG-PLLA copolymers by two methods i.e. nanoprecipitation and double emulsion solvent evaporation. The nanoprecipitation method showed very less entrapment and polymer solubility in the acetone-water mixture leading to uncontrolled polymer precipitation. The difficulties encountered in the nanoprecipitation method were overcome with the help of the double emulsion (w/o/w) solvent evaporation technique. It has been observed from the results that biodegradable copolymer nanoparticles protect the drug from degradation and also help in controlling the release of encapsulated drug. The properties of nanoparticles can be tailored by varying the composition of mPEG in order to get improved entrapment efficiency and desired drug release. The nanoparticles were assessed for their in vitro cytotoxicity (MTT and FACS) and cellular uptake (fluorescence microscopy) study which showed very promising results. Nanoparticles were also studied for their in vivo release after intravenous administration to Wistar albino rats, which successfully showed controlled drug release for more than 14 days.